(untitled) (UNED Research Journal, 2016)
Tropical plants have a diverse morphology and physiology adapted to capture light within the forest. Piper retuculatum is a small tree that grows in illuminated and low light environments. We randomly collected 25 mature leaves from each condition (from several plants), and determined the specific leaf area (SLA), leaf thickness and shape; and amount of chlorophyll. Plants from both light classes differed in SLA, thickness, shape and chlorophyll content of the leaves. Those exposed to light had higher values for shape and thickness while low light plants had leaves with more SLA and chlorophyll content values. P. reticulatum presents great plasticity for leaf shape which increases its performance and allows it to compete with advantage against other plant species.